PROFESSIONAL EXAMINATIONS. - Chamberlain, Henry T.; Chamberlain, John H. (The Accounting Review, 1960)
The article presents accounting problems prepared by the Board of Examiners of the American Institute of Certified Public Accountant (CPA) and were presented as the second half of the CPA examination in accounting practice in November 5, 1959. The candidates ere required to solve the problems 1 and 2 and any two of the remaining three problems. The first problem is related to preparation of cost study to determine economical feasibility of a publishing company. The second question is related to deriving reasons for the changes in the working capital of a company from its balance sheet. It requires application of funds statement, supported by a schedule of working capital changes and a cash flow statement, supported by a schedule detailing the cash provided or applied by profits or losses from operation. The third problem requires preparation of a schedule of labor production, total and unit costs incurred in production and schedule of detailed material labor and manufacturing costs assigned to the units left in process.